Which features of thin melanomas make them more likely to cause death. (31st March 2020) - Claeson, M.; Baade, P.; Brown, S.; Soyer, H.P.; Smithers, B.M.; Green, A.C.; Whiteman, D.C.; Khosrotehrani, K.
Summary: Skin cancer is the most common cancer in Western populations. Melanoma is the most dangerous form of the disease. Melanoma tends to grow in 'thickness' (depth of invasion into the skin) if left untreated, and thicker tumours are considered more advanced and harder to treat than thinner tumours. However, around one quarter of all deaths from melanoma in Queensland, Australia are caused by thin tumours, invading the skin's surface to a thickness of 1mm or less (≤1.00 mm). This study aimed to find factors that, at diagnosis, can identify patients who will eventually die from thin melanoma. Data from the Queensland Cancer Registry were analysed to compare the characteristics of 424 thin melanomas that caused the patient to die to 1, 189 thin melanomas that did not lead to death. Thin melanomas located on the scalp were six times more likely to cause the patient's death, when they were compared to thin melanomas on the back. Also, the thicker of the thin melanomas, which penetrated the skin to 0.80‐1.00 mm thickness, were six times as likely to cause death, when compared to minimally invasive (thinner) tumours with a thickness of less than 0.30mm. This study showed that where on the body the tumour occurs, and increasing thickness, could identify the more dangerous tumours among the thin melanomas, at diagnosis. Patients with melanomas with these characteristics may need closer follow‐up after diagnosis and treatment. This is a summary of the study: Clinicopathological factors associated with death from thin (≤ 1.00 mm) melanoma